(3JMQjQ GdbhGYO GdefWbjI aj TQM GdQSGdI GdTeSjIs - (3GdQGRj, CHh YHO Gddg, bWH GdOjf, eMeO (B((3Ch eMehO(B) (3Hf eMeO, J (B766 (3g`s ((3eMeO egOj Hf YHO GdUeOs)
(3ChdgG (B:s
...(3HBjGJ hLhH hLhOg hTcQ efYe CZQb GdeNdhbGJ aj HMGQ CaVGdg hLhOg(B...s
(3BNQgG (B:s
(3adGHO Cf jchf NGQLjI Yf GdehVhYGJ dGeJfGY Cf jchf LRA GdTjA eWdhHG HGdHQgGf(B...s
(3JNJda eSWQJg aGdChQGb GdChdi ef GdcJGH eSWQJgG KdGKI YTQ SWQG(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B7(3,U(B38s
(3EjVGM Gdecfhf(B:(3L(B1(3,U(B233s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdadSaI hGdefWbs